A Meta-Synthesis of Research on Achievement-Oriented Leadership Style: Ihsan Values Lens - Sodikin, Mohamad; Fachrunnisa, Olivia; Nurhidayati (International Journal of Economics, Management and Accounting, 2022)
This study aims at revising the achievement-oriented leadership style of the path-goal leadership theory by intervening with an Islamic ethical value that has transcendental meaning. Several studies concerning achievement-oriented leadership styles have been conducted, but they have not been based on transcendental values. They are still oriented toward transactional, material, and worldly achievements. The literature review on path-goal leadership theory covering 1996-2020 was carried out, especially on the achievement-oriented leadership dimension. Qualitative methods were used in this study to review several articles related to purpose of this study. The Publish or Perish application from Harzing (Adams, 2016) filtered the relevant article data. This study involved two databases, namely Scopus and Google Scholar and it obtained 104 articles with 89 articles from Google Scholar and 15 from Scopus. The review was done concerning the research objectives. In the end, five articles were analyzed based on achievement-oriented leadership. The existing literature shows that achievement-oriented leadership does not yet have transcendental Islamic spiritual values. Therefore, it is necessary to augment it with transcendental values, such as “Ihsan”. This study fills existing theoretical gaps and provides new insight into achievement-leadership style. In addition, it introduces a new leadership model, namely Ihsan's achievement-oriented leadership, which can provide better practical management skills to leaders. This study contributes to improving the literature on leadership styles based on Islamic values, especially Ihsan values. Future studies may consider developing the measurement and validation instrument of Ihsan's achievement-oriented leadership concept.